PERENCANAAN KONSTRUKSI SHEET PILE WALL SEBAGAI ALTERNATIF PENGGANTI GRAVITY WALL(Studi Kasus Proyek Sindu Kusuma Edupark, Yogyakarta) - Isti Radhista Hertiany, Adwiyah Asyifa (Universitas Negeri Yogyakarta, 2014)
In the recent decade , the development of retaining wall construction keeps growing rapidly along the optimization of the use of available land. The main purpose of this construction is restrain the land so as not landslide Due to the load that it work in addition to the utilization of the space available. In this case study in sindu kusuma edupark project using construction type anchoring ground gravity wall. If the structure of gravity wall is not safe withstand the force that worked , then required alternative design construction of retaining wall of another appropriate. Construction retaining wall that can be used as alternatives is sheet-pile wall or commonly called Turap. The difference of gravity wall and turap lies in the stability analysis of construction and materials. Excess of sheet pile of this wall is the tough a lighter , the implementation of the gravity relatively quickly than wall, Suitable used for the drift the ground with a height was , the quality of construction uniform and more secured construction than manual for using prefabricated construction. From the analysis of stability gravity wall , we can conclude that when the structure receives of static load, Construction stability was not secure against overtuning , sliding , axial load , and broken foot structure but it still safe receives sliding and capacity stability fulfilled. When encumbered by dynamic loads, structure safe against bolsters, sliding, and soil bearing capacity.The Sheet pile wall selected as a substitute for wall gravity is prefabricated concrete Wika Beton , with type w-325 a 1000 - length: 8 m with a long as deep as 3 m of installing. The type of sheet pile used anchorage sheet pile of continuous type, with 10 mm in diameter and the distance is 3m. The Boards anchor used behind construction sheet-pile with 3m in long sized, make stability sheet-pile secure with SF = 2.Key word: Pile wall, Safety Factor